(untitled) (Eurasian Journal of Religious Studies, 2017)
In this article, the author examines the problem of the correlation and interrelationship between postmodernism and religion, the features of postmodern religion. Religion for thousands of years fastened the society, united people, made their life meaningful, inhaled the meaning and animated all human relations. What happens to it in postmodern conditions? Does it remain a bastion of resistance to the corrupting influence of postmodernism? It is doomed to disappear or just to metamorphize when society moves to its postmodern stage? The author tries to analyze the state and solution of the issue in modernism and postmodernism, their difference.